THE SIXTH COMMUNICATION REVOLUTION AS A FACTOR IN THE TRANSFORMATION OF MANAGEMENT AND THE DIGITAL ECONOMY - Маханець, Любов; Філіпчук, Наталія; Маханець, Богдан (SWorldJournal, 2026)
The paper examines the sixth communication revolution as a new stage in the development of the digital economy, shaped by the integration of artificial intelligence, next-generation networks, and virtual and augmented environments. It is argued that mode